The Efficacy and Safety of Endoscopic Ultrasound-Guided Celiac Plexus Neurolysis for Treatment of Pain in Patients with Pancreatic Cancer - Anna Wiechowska-Kozłowska; Klaudiusz Boer; Maciej Wójcicki; Piotr Milkiewicz (Gastroenterology Research and Practice)
Introduction. Celiac plexus neurolysis is used in pain management of patients with advanced and unresectable pancreatic cancer. We retrospectively analyzed efficacy and safety of endoscopic ultrasound- (EUS-) guided celiac plexus neurolysis in patients treated in our unit. Methods. Twenty nine subjects with unresectable pancreatic cancer and severe pain despite pharmacological treatment underwent EUS-guided celiac plexus neurolysis with 98% ethanol. Patients scored their pain according to a 0–10 point scale and were interviewed 1-2 weeks and 2-3 months after the procedure. Results. Twenty five (86%) patients reported improvement in their pain at 1-2 weeks following the procedure. Of these, 7 (24%) reported substantial improvement (decrease in pain by more than 50%) and 4 (14%) complete disappearance of pain. Pain relief was still present in 76% of patients after 2-3 months. Treatment-related side effects included hypotonia in 1 patient, severe pain immediately postprocedure in 2 patients, and short episodes of diarrhea in 3 patients. Conclusion. Endoscopic ultrasound- (EUS-) guided celiac plexus neurolysis is a safe and effective treatment of severe pain from advanced pancreatic cancer.